Preparation of a fluorinated dental resin system and its anti-adhesive properties against S. mutans. Issue 4 (April 2023) - He, Jingwei; Stenhagen, Ida S.R.; Dragland, Inger S.; Kopperud, Hilde M.
Abstract: Objectives: The purpose of this study was to characterize physicochemical properties and investigate anti-bacterial adhesion effect of dental resins containing fluorinated monomers. Method: Fluorinated dimethacrylate FDMA was mixed with commonly used reactive diluent triethylene- glycol dimethacrylate (TEGDMA) and fluorinated diluent 1 H, 1 H-heptafluorobutyl methacrylate (FBMA) separately at a mass ratio of 60 wt./40 wt. to prepare fluorinated resin systems. Double bond conversion (DC), flexural strength (FS) and modulus (FM), water sorption (WS) and solubility (SL), contact angle and surface free energy, surface element concentration, and anti-adhesion effect against Streptococcus mutans ( S. mutans ) were investigated according to standard or referenced methods. 2, 2-bis[4-(2-hydroxy-3-methacryloy-loxypropyl)-phenyl]propane (Bis-GMA)/TEGDMA (60/40, wt./wt.) was used as control. Results: Both fluorinated resin systems had higher DC than Bis-GMA based resin ( p  < 0.05); compared with Bis-GMA based resin (FS, FDMA/TEGDMA resin system had higher FS ( p  < 0.05) and comparable FM ( p  > 0.05), while FDMA/FBMA resins system had lower FS and FM ( p  < 0.05). Both fluorinated resin systems had lower WS and SL than Bis-GMA based resin ( p  < 0.05), and FDMA/TEGDMA resin system had the lowest WS ( p  < 0.05) in all experimental resin systems. Only FDMA/FBMA resin system showed lower surface free energy than Bis-GMA based resin ( p  < 0.05). When the surface was smooth, FDMA/FBMA resin system had lower amount of adherent S. mutans than Bis-GMA based resin ( p  < 0.05), while after the surface became roughness, FDMA/FBMA resin system had comparable amount of adherent S. mutans as Bis-GMA based resin ( p  > 0.05). Significance: Resin system prepared exclusively with fluorinated methacrylate monomers reduced the S. mutans adhesion due to their increased hydrophobicity and decreased surface energy., while flexural properties of it should be improved.